Fragile X Associated Primary Ovarian Insufficiency (FXPOI): Case Report and Literature Review - Fink, Dorothy A.; Nelson, Lawrence M.; Pyeritz, Reed; Johnson, Josh; Sherman, Stephanie L.; Cohen, Yoram; Elizur, Shai E. (Frontiers in Genetics, 2018)
Abnormalities in the X-linked FMR1 gene are associated with a constellation of disorders, which have broad and profound implications for the person first diagnosed, and extended family members of all ages. The rare and pleiotropic nature of the associated disorders, both common and not, place great burdens on 1) the affected families, 2) their care providers and clinicians, and 3) investigators striving to conduct research on the conditions. Fragile X syndrome, occurring more severely in males, is the leading genetic cause of intellectual disability. Fragile X associated tremor and ataxia syndrome (FXTAS) is a neurodegenerative disorder seen more often in older men. Fragile X associated primary ovarian insufficiency (FXPOI) is a chronic disorder characterized by oligo/amenorrhea and hypergonadotropic hypogonadism before age 40 years. There may be significant morbidity due to: 1) depression and anxiety related to the loss of reproductive hormones and infertility; 2) reduced bone mineral density; and 3) increased risk of cardiovascular disease related to estrogen deficiency. Here we report the case of a young woman who never established regular menses and yet experienced a 5-year diagnostic odyssey before establishing a diagnosis of FXPOI despite a known family history of fragile X syndrome and early menopause. Also, despite having clearly documented FXPOI the woman conceived spontaneously and delivered two healthy children. We review the pathophysiology and management of FXPOI. As a rare disease, the diagnosis of FXPOI presents special challenges. Connecting patients and community health providers with investigators who have the requisite knowledge and expertise about the FMR1 gene and FXPOI would facilitate both patient care and research. There is a need for an international natural history study on FXPOI. The effort should be coordinated by a global virtual center, which takes full advantage of mobile device communication systems.